Electrochemical One-Pot Synthesis of Cyclic Oligoglucosamines - Endo, Hirofumi; Rahman, Azadur MD; Masaharu, Ochi; Hamada, Tomoaki; Kawano, Takahiro; Sasaki, Norihiko; Nokami, Toshiki (Meeting abstracts (Electrochemical Society), 2024)
Carbohydrates are known as the third chain of life, following DNA and proteins, and their roles extend beyond energy and structural materials to function as pharmaceuticals and cell recognition molecules (1 . Among carbohydrates, sugar chains that undergo intramolecular glycosylation are called cyclic oligosaccharides; for example, cyclodextrins are a well-known example composed of six or more D-glucose unit. By utilizing the inclusion ability and molecular recognition ability of the cavities within cyclodextrins, applications such as drug delivery systems, functional materials, and pharmaceuticals have been developed (2 . These functional developments are achieved through functional group transformations, although the adaptability of these transformations is partially challenging from the perspective of identifying the reactivity of hydroxyl groups. Therefore, for further functional development, a bottom-up synthesis starting from the monosaccharide is required. We have been focusing on the synthesis of cyclic oligosaccharides using D-glucosamine, which has an amino group at the 2-position of the pyranose ring (3 . Although cyclic oligosaccharides are essentially repetitions of the same monosaccharide, sequential synthesis is required to distinguish between elongation and cyclization, leading to redundancy in the synthetic process. Therefore, we have focused on an organic electrochemical method (4 , where we can control the initiation and termination of reactions by passing electric currents. To control both elongation and cyclization in one-pot, we synthesized building blocks containing 2,3-oxazolidinone, known to change its structure from the β-form to the α-form through thermodynamically controlled isomerization using acid (5 . Using this building block, we achieved the synthesis of cyclic oligosaccharides containing α-1,4-glycosidic bonds from D-glucosamine in one-pot through a combination of two-stage electrolysis and acid-induced isomerization (6 ( Figure a. ). We will also present the α-selective synthesis of disaccharides containing oxazolidinone protecting groups, which significantly affect the formation of the cyclic structure, and their one-pot synthesis aiming to expand the substrate scope of cyclic oligosaccharides. We are also conducting research on establishing an electrochemical one-pot synthesis for β-1,6-cyclic oligoglucosamine, in addition to cyclic oligosaccharides containing α-1,4-glycosidic bonds. By introducing different protecting groups to the amino group of glucosamine and its hydroxyl groups, we have achieved control over the cyclic structure and polymerization degree of the products ( Figure b. ). 1) Varki, A. Glycobiology , 2017 , 27 , 3. 2) Szejtli, J. Chem. Rev. , 1998 , 98 , 1743. 3) Nokami, T. et al. , Chem. Rec. , 2021 , 21 , 2389. 4) Baran, P. S. et al. , Chem. Rev. , 2017 , 117 , 13230. 5) Kerns, R. J. et al. , J. Am. Chem. Soc. , 2001 , 123 , 9461. 6) Nokami, T. et al. , Chem. Commun. , 2022 , 58 , 7948. Figure 1